2020
DOI: 10.31665/jfb.2020.9215
|View full text |Cite
|
Sign up to set email alerts
|

Should the in vitro colorimetric assays in antioxidant and lipid oxidation evaluation be abandoned? A critical review focusing on bioactive molecule screening assays in in vitro and in vivo models

Abstract: Increasing evidence has proven the potent antioxidative effectiveness of bioactives in natural products for preventing/suppressing chronic diseases. In this connection, the development of efficient methods that are suitable to screen bioactives in vitro and in vivo tests has taken place.  Thus, a variety of assays have been used in the extraction of bioactives, testing of their antioxidant potential in both in vitro and in vivo model, and evaluating lipid oxidation are comprehensively discussed here. This revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 138 publications
0
5
0
Order By: Relevance
“…Purple sweet potato is rich in anthocyanins, which are natural powerful free radical scavengers, and their clearing ability is 20 times than that of vitamin C (Pascual‐Teresa & Sanchez‐Ballesta, 2008). D. melanogaster has a lipid metabolism and transport system similar to that of mammalian hepatocytes, which can explore the mechanism of regulating basic biological processes and is beneficial to the study of biological activity (Shahidi & Yeo, 2020). LC‐MS analysis of PSPE found that it contained multiple anthocyanins, which made purple sweet potatoes to have multiple biological activities, such as anti‐inflammation, anti‐cancer, and anti‐oxidation (Kano et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Purple sweet potato is rich in anthocyanins, which are natural powerful free radical scavengers, and their clearing ability is 20 times than that of vitamin C (Pascual‐Teresa & Sanchez‐Ballesta, 2008). D. melanogaster has a lipid metabolism and transport system similar to that of mammalian hepatocytes, which can explore the mechanism of regulating basic biological processes and is beneficial to the study of biological activity (Shahidi & Yeo, 2020). LC‐MS analysis of PSPE found that it contained multiple anthocyanins, which made purple sweet potatoes to have multiple biological activities, such as anti‐inflammation, anti‐cancer, and anti‐oxidation (Kano et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…De Camargo et al [ 183 ] encouraged the scientific community to determine bioactive compounds by employing at least some in vitro biological methods (e.g., cell lines) and also contemplating simulated digestion; although, in vivo assessment has been regarded as being most preferred. The general aspects and the pros and cons of antioxidant methods have already been addressed [ 185 , 186 , 187 ]. Nevertheless, one should always bear in mind the primary purpose of each study.…”
Section: Antioxidant Capacity Of Rice Wheat and By-products Thereofmentioning
confidence: 99%
“…Interferences from non-polyphenolic components can also cause false readings and thus lead to erroneous results. For instance, some amino acids, metal ions and other reducing substances present in the sample have reducing powers and therefore can reduce chemical indicators such as DPPH (Tsao, 2010;Shahidi and Yeo, 2020). These methods should therefore only be used as a preliminary assessment of phenolic contents prior to more thorough chromatographic evaluation (Panche et al, 2016;Shahidi and Yeo, 2020).…”
Section: Spectrophotometrymentioning
confidence: 99%